2023
DOI: 10.3390/su151612245
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Varying Combinations of Dietary Selenium, Vitamin E, and Zinc Supplements on Antioxidant Enzyme Activity, and Developmental and Histological Traits in Testicular Tissues of 1-Year-Old Native Turkish Ganders

Abstract: The aim of this study was to determine the effects of varying combinations of dietary selenium (Se), vitamin E (Vit E), and zinc (Zn) supplements on antioxidant enzyme activity, and developmental and histological traits in testicular tissues of 1-year-old native Turkish ganders. A total of 48 animals were used and randomly assigned to 8 treatment groups (control, Se, Vit E, Zn, Se + Vit E, Se + Zn, Vit E + Zn, and Se + Vit E + Zn), with 6 birds in each group. In addition to the control (basic) diet, specific l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Compared to the control group, the combined supplementation of Se + Vit E + Zn to diet, rather than using each separately, had a synergistic effect on sperm quality characteristics and increased semen volume, sperm concentration, sperm motility, and SQF values by 40%, 15.5%, 16.2%, and 79%, respectively. This improvement in semen quality is quite consistent with our results in Baş et al [26], the first study in which we revealed the histological parameters and oxidative enzyme activity in the testicular tissue of 1-year-old native Turkish ganders.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to the control group, the combined supplementation of Se + Vit E + Zn to diet, rather than using each separately, had a synergistic effect on sperm quality characteristics and increased semen volume, sperm concentration, sperm motility, and SQF values by 40%, 15.5%, 16.2%, and 79%, respectively. This improvement in semen quality is quite consistent with our results in Baş et al [26], the first study in which we revealed the histological parameters and oxidative enzyme activity in the testicular tissue of 1-year-old native Turkish ganders.…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant enzyme activity of the testicular tissue found in Baş et al's [26] study and the enzyme activity levels of the sperm cells determined in this study were quite parallel. Thus, by reducing oxidative damage in testis tissues with antioxidative feeding (Se, Vit E, Zn) in ganders, seminiferous tubule area and diameter and germinal cell layer thickness increased and the relative area of interstitial tissue decreased, which promoted the increase of sperm production and quality, which was also consistent with Malaniuk and Lukaszewicz [40], Edens and Sefton [41] and Baş et al [26]. The variation of sperm quality and antioxidant enzyme activity parameter values obtained according to treatments in this study is also consistent with previous studies [9,29].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Bas et al. ( 2023 ) reported that vitamin E, Zn and Se minerals added to the feed of Turkish geese at different ratios positively improved SOD, catalase, GSH peroxidase and GSH‐ S ‐transferase activities in testicular tissues but had no effect on MDA levels. Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), and malondialdehyde (MDA) were measured [40].…”
Section: Antioxidant Enzymes and Malondialdehyde In Testes Tissuementioning
confidence: 99%